Comparison of physiological and 2D kinematic variables during 2KM time trial on stationalry versus dynamic rowing ergometers - Zahiran, A.; Abdullah, M. I.; Shaharudin, S. (Malaysian Journal of Movement, Health and Exercise, 2019)
This study was conducted to evaluate the differences of physiological and biomechanical variables during 2km rowing time trial on stationary versus dynamic ergometer. Ten state-level rowers (male: 6, female: 4) were voluntarily participated in the study. Two sessions of 2km time trial were conducted: one on a static ergometer while another on a dynamic ergometer. Data on oxygen consumption, blood lactate concentration, maximum heart rate, stroke rate, time to completion and lower limb angles at sagittal plane were collected and analysed during the tests. Paired T-test was used to compare the physiological and biomechanical variables across stationary and dynamic ergometer. Stroke rate, maximum heart rate, drive to recovery phase ratio and VO2max showed statistically significant differences during 2km rowing time trial on stationary versus dynamic ergometer. Moreover, VO2max was inversely related with high correlation to time to completion of 2km rowing test on both ergometer. Height, body fat and VO2max are the major determinants of 2 km rowing time trial on stationary and dynamic ergometer. The outcomes from this study are important to enhance rowing performance especially for rowers.